Severe Outcomes, Readmission, and Length of Stay Among COVID-19 Patients with Intellectual and Developmental Disabilities. (March 2022) - Koyama, Alain K.; Koumans, Emilia H.; Sircar, Kanta; Lavery, Amy; Hsu, Joy; Ryerson, A. Blythe; Siegel, David A.
Highlights: Intellectual and developmental disabilities may predict worse COVID-19 outcomes. Down syndrome conveyed more than a 2-fold increased risk of mortality from COVID-19. Autism spectrum disorders were associated with longer COVID-19 hospitalizations. Abstract: Objectives: The aim of this study was to evaluate the association between intellectual and developmental disabilities (IDDs) and severe COVID-19 outcomes, 30-day readmission, and/or increased length of stay (LOS) using a large electronic administrative database. Methods: Patients hospitalized with COVID-19 were identified between March 2020 and June 2021 from more than 900 hospitals in the United States. IDDs included intellectual disability, cerebral palsy, Down syndrome, autism spectrum disorder (ASD), and other intellectual disabilities. Outcomes included intensive care unit (ICU) admission, invasive mechanical ventilation (IMV), 30-day readmission, mortality, and LOS. Results: Among 643, 765 patients with COVID-19, multivariate models showed that patients with any IDD were at a significantly greater risk of at least 1 severe outcome, 30-day readmission, or longer LOS than patients without any IDD. Compared with those without any IDD, patients with Down syndrome had the greatest odds of ICU admission (odds ratio [OR] and 95% confidence interval [CI]: 1.96 [1.73-2.21]), IMV (OR: 2.37 [2.07-2.70]), and mortality (OR: 2.33 [2.00-2.73]). Patients with ASD and those with Down syndrome both had over a 40% longer mean LOS. Patients with intellectual disabilities had a 23% (12-35%) increased odds of 30-day readmission. Conclusions: Results suggest that patients hospitalized with COVID-19 with IDD have a significantly increased risk of severe outcomes, 30-day readmission, and longer LOS.